An Early Warning System for Currency Crisis: A Comparative Study for the Case of Jordan and Egypt - Al-Assaf, Ghazi (International Journal of Economics and Financial Issues, 2017)
The paper investigates the differences between number of indicators used for an early warning system to explain any potential currency crisis for the case of Jordan and Egypt. The comparison is based on estimating various leading indicators that help in predicting the currency crises in the countries under investigation. A market pressure index (MP) was constructed and employed in a multinomial Logit model, using monthly data for Jordan and Egypt covering the period 1980-2015. The empirical results, show that real exchange rate (RER), money supply-reserves ratio (M2R), growth rate of domestic credit (âˆ†DC), Central Bank foreign assets to liabilities ratio (AL), and growth of exports play a significant role in explain the currency crises for both Jordan and Egypt economies. However, the money supply-reserves ratio is the one of the most significant indicators in predicting currency crisis for Jordan, while the real exchange rate is found for the case of Egypt. Keywords: Early Warning Systems, Currency Crisis, Logit Model, Jordan, Egypt. JEL Classifications: F31, F47, C53